Manifestações do amor materno : as maternidades representadas em contos de Conceição Evaristo - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
In this research, I analyze the myth of maternal love in the different form s of motherhood in the short stories “Shirley Paixão” and “Saura Benevides Amarantino”, from Insubmissas lágrimas de mulheres (2016), and in “Quantos filhos did Natalina teve?”, from Olhos d’água (2020), by the author Conceição Evaristo. The analysis seeks to understand the different manifestations of maternal love in the stories of motherhood represented in Evaristo’s narratives, demonstrating how the intersectionality of patriarchal and racist power relations influence the lives of the protagonists. The m ethodological structure is based on a review of specialized criticism that addresses the theme of maternal love in Evaristo's fiction, followed by a deeper understanding of the concept of maternal love through a bibliographic review of theorists who are fu ndamental to discussions around the mothering of black women in and outside of fiction, such as Angela Davis (2016; 2019), Antonio Candido (2014; 2023), bell hooks (2019), Carla Akotirene (2019), Elisabeth Badinter (1985; 2022), Gerda Lerner (2019), Joice Berth (2020), and Pierre Bourdieu (2012). Therefore, in this study, in addition to analyzing the selected short stories, focusing on the intersectionality between maternal love, race, and gender, I also discuss maternal love as a form of existential affirm ation and resistance against the oppressive status quo, and as an act of freedom.
Manifestations of maternal love : the motherhoods represented in tales of Conceição Evaristo
Keywords: Literatura brasileira contemporânea; Conceição Evaristo; Maternidade; Interseccionalidade; Mulheres negras; Contemporary brazilian literature; Motherhood; Intersectionality; Black women; LINGUISTICA, LETRAS E ARTES; LETRAS::LITERATURA BRASILEIRA